From phytomedicine to photomedicine: quercetin-derived carbon nanodots—synthesis, characterization and healthcare applications - Naik G.G.; Pratap R.; Mohapatra D.; Shreya S.; Sharma D.K.; Parmar A.S.; Patra A.; Sahu A.N. (My University, 2025)
In this report, we present the hydrothermal method-driven synthesis of carbon nanodots (CNDs) using quercetin and further evaluate the effects of surface passivation on their physicochemical and biological attributes. The quercetin-derived CNDs (qCD) were surface passivated with polyethylene glycol to produce qCD-Pg. Firstly, the qCD was employed as a fluorescent nanoprobe that can selectively sense arsenic (As3+) with a limit of detection (LOD) of 0.598 μM through enhancement in fluorescence emission. It was revealed that upon surface fabrication with polyethylene glycol, qCD lost its ability to sense As3+, but qCD-Pg selectively detected iron (Fe3+) with a LOD of 0.324 μM. The developed method was validated as per International Conference on Harmonization Harmonised Tripartite Guideline (ICH Topic Q 2 (R1). The applicability of the qCD and qCD-Pg-based sensing method for the quantification of As3+ and Fe3+ in a real sample (tap water) was also analyzed. Further, the qCD-Pg was conjugated with andrographolide (Ad) to produce qCD-Pg-Ad and explored as a nanocarrier for its delivery. These conjugates prolonged and improved the drug release, leading to an enhanced cytotoxic effect on leukemia cancer cells (K-562). Also, the qCD-Pg-Ad complex had a better anticancer effect on K-562 than free form and showed very low cytotoxicity to normal kidney cells (Vero), indicating specific anticancer activity to the leukemia. These CNDs considerably inhibited the growth of multi-drug resistant bacterial strains and exhibited significant free radical scavenging potential. These nanodots showed good thermal stability, colloidal dispersion stability, and photostability. Overall, the findings of our study demonstrated phytomedicine-derived CNDs as photomedicine with broad applications in biomedical and environmental domains. Graphical abstract: [Figure not available: see fulltext.]. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.